HUBUNGAN KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT DI KECAMATAN BANJARMASIN BARAT KOTA BANJARMASIN - Junaidy Inas, M. IKom., M.AB Junaidy; Murdiansyah Herman Murdiansyah Herman; Sugiannor Sugiannor (Jurnal Ilmiah Ekonomi Bisnis, 2020)
Quality of service emphasizes the orientation of fulfilling public satisfaction in general in Banjarmasin Barat Subdistrict, Banjarmasin City. In this research, quality of service is the main focus to find a relationship with public satisfaction. This research uses a descriptive quantitative approach with survey data collection procedures. Research location at Banjarmasin Barat Subdistrict Office. The measuring scale used in this study is the Likert Scale. Determination of samples in this study uses the probability sampling methode. Based on the result and discussion of data, quality of service not spread at all level of categories from Chi Square Goodness of Fit (X2 = 59,750; p = 0,000). These results are compared with table X2 with a significance level of 5% is 12,592. So, X2 count value is greater than X2 table (59,750 > 12,592). Public satisfaction not spread at all level of categories with X2 count value is 19,000 with level of categories value is 0,025. These result are compared with table X2 with a significance level of 5% is 16,919. So, X2 count value is greater than X2 table (19,000 > 16,919). Quality of service and satisfaction level (0,204 > 0,05) has a relationship, therefore quality of service and public satisfaction has a relationship too.